Transvaginal natural orifice endoscopic surgery for ovarian cystectomy: a more suitable surgical approach for the day-care procedure - Xie, Aijie; Li, Xin; Huang, Juan; Wang, Hui; Liu, Ying; Wang, Lulu; Liao, Jianmei; Yu, Jie; Yan, Ziru; Zhang, Jiajia; Huang, Liqiong; Liu, Tianjiao; et al. (Frontiers in Medicine, 2023)
Introduction: Although previous studies have shown that vaginal natural orifice transluminal endoscopic surgery (vNOTES) have the advantages of less pain, faster recovery, and better concealment of surgical incisions, which aligns with the concept of day-care procedure, this approach poses a greater risk of damaging adjacent organs (i.e., rectum and bladder) due to its anatomical specificity. Moreover, day-care procedure may lead to relatively less preoperative evaluation and postoperative care. Hence, it is necessary to explore the safety and effectiveness of vNOTES for ovarian cystectomy in day-care procedure, to provide theoretical basis for the wider development of vNOTES surgery. Material and methods: This retrospective study included 131 patients at our hospital who underwent ovarian cystectomy from September 2021 to October 2022. Based on the surgical approach, patients were classified into transumbilical laparoendoscopic single-site surgery (LESS) and vNOTES groups. The patients’ demographic characteristics and follow-up data were collected during the perioperative period and at one month postoperatively. Results: vNOTES have less postoperative exhaust time, lower postoperative 6-hour pain score and incidence of analgesic drug use, with the higher surgical conversion incidence. Multiple linear regression analysis showed that the surgical conversion, chocolate cyst, bilateral cyst, and pelvic adhesion increased the operation duration by approximately 43 (95% CI: 10.309, 68.152, p<0.001), 15 (95% CI: 6.342, 45.961, p=0.036), 10 (95% CI: 3.07, 40.166, p=0.019), 8 (95% CI: 4.555, 26.779, p=0.035) minutes, respectively. Interestingly, vNOTES decreased the operation duration by approximately 8.5 minutes (95% CI: -18.313, -2.699, p=0.033). Conclusions: vNOTES was equally safe and effective for ovarian cystectomy compared to that of LESS. vNOTES aligned with the concept of day-care procedure due to its reduced postoperative pain, shorter exhaust time, and absence of scarring. However, surgeons should conduct a comprehensive preoperative evaluation and exclude patients suspected to have severe pelvic adhesions.